Silica-Based Gene Delivery Systems: From Design to Therapeutic Applications - Carvalho, Ana Maria (2020)
Advances in gene therapy have been foreshadowing its potential for the treatment of a vast range of diseases involving genetic malfunctioning. However, its therapeutic efficiency and successful outcome are highly dependent on the development of the ideal gene delivery system. On that matter, silica-based vectors have diverted some attention from viral and other types of non-viral vectors due to their increased safety, easily modifiable structure and surface, high stability, and cost-effectiveness. The versatility of silane chemistry and the combination of silica with other materials, such as polymers, lipids, or inorganic particles, has resulted in the development of carriers with great loading capacities, ability to effectively protect and bind genetic material, targeted delivery, and stimuli-responsive release of cargos. Promising results have been obtained both in vitro and in vivo using these nanosystems as multifunctional platforms in different potential therapeutic areas, such as cancer or brain therapies, sometimes combined with imaging functions. Herein, the current advances in silica-based systems designed for gene therapy are reviewed, including their main properties, fabrication methods, surface modifications, and potential therapeutic applications.